Promoting Responsible Vehicle Ownership to Prevent Underage Driving and Motorcycling: A Legal Solution for Indonesia - Tantimin, Tantimin; Jaya, Febri; Tan, David; Fitri, Winda (Kosmik Hukum, 2025)
This study aims to address and ultimately find the solution to the phenomenon of underage driving and motorcycling in Indonesia. The continued rise of vehicle ownership has also increased the risks of traffic accidents, which are then exacerbated by the phenomenon of underage driving and motorcycling. Ultimately, this has raised the urgency to thoroughly analyze the causes behind this phenomenon and explore other legal angles to curb this problem and increase the safety of all road users. Through the normative legal research method with statutory approach, this study finds that there are normative inadequacies within the relevant legal framework to tackle the issue of underage driving and motorcycling. This study also proposes a strategy to help tackle this problem by focusing on holding vehicle owners more accountable with a structured penalty system directly to the owners of the vehicles, as they are enabling this dangerous behavior.